A Giant Solitary Adrenal Plasmacytoma in a Patient with HIV: A Rare Case Report and Review of the Literature. (3rd February 2021) - Chennoufi, Mehdi; Boukhannous, Ibrahim; Mokhtari, Mohamed; El Moudane, Anouar; Irzi, Mohamed; Ouraghi, Abdelghani; Jandou, Issam; Miry, Achraf; Barki, Ali
Abstract : Solitary extramedullary plasmacytoma (EMP) involving the adrenal gland is an extremely rare malignancy. We report a case of a solitary adrenal plasmacytoma in an HIV-positive 50-year-old woman on antiretroviral therapy who presented with a rapidly progressing lumbar left masse. A CT scan objectified a locally advanced left adrenal mass measuring 135mm long axis. A biopsy was taken, and the histopathology with the immunohistochemical study objectified an adrenal gland plasmacytoma. The skeletal survey and the sternal suction biopsy did not show any abnormalities. The diagnosis of a solitary EMP of the adrenal gland was made. There are only 10 cases of solitary adrenal plasmacytoma with only one case associated with an HIV-positive patient reported in the literature. Therefore, this paper is aimed at presenting the second case of an HIV-positive patient diagnosed with solitary adrenal plasmacytoma.